2012
DOI: 10.1111/j.1601-5215.2012.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted cognitive remediation in adolescents with psychosis or at risk for psychosis: a 6-month follow-up

Abstract: Objective: To investigate short-term outcomes of a computer-assisted cognitive remediation (CACR) for adolescents with psychotic disorders or at high risk for psychosis. Method: Cognitive abilities and clinical status were assessed at baseline (N = 32) and at 6-month follow-up (N = 22) after enrolment in either a CACR (treatment group) or a computer games (control group) program (8 weeks). Results: With regard to the cognitive abilities, no amelioration was found in the control group while, in the CACR group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 46 publications
(62 reference statements)
0
25
1
Order By: Relevance
“…The results indicate that prodromal patients can improve their long-term verbal memory, attention, and concentration after cognitive training. Another study investigated short-term outcomes of CACR in adolescents with psychotic disorders or at high risk of psychosis [41]. The analysis of data revealed significant differences between baseline and followup in executive function and reasoning abilities, with better performances at followup only in the CACR group.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that prodromal patients can improve their long-term verbal memory, attention, and concentration after cognitive training. Another study investigated short-term outcomes of CACR in adolescents with psychotic disorders or at high risk of psychosis [41]. The analysis of data revealed significant differences between baseline and followup in executive function and reasoning abilities, with better performances at followup only in the CACR group.…”
Section: Resultsmentioning
confidence: 99%
“…However, the training failed to yield improvements in depression symptoms, and other results suggest that clinical benefits of such a training can only be observed when administered in conjunction with psychotherapy (Bowie et al, 2013). Several studies have demonstrated that high-frequency, computerized cognitive training ameliorates deficits in cognitive flexibility among those with schizophrenia (Bellucci, Glaberman, & Haslam, 2003; Dickinson et al, 2010; Urben et al, 2012). Results on generalization of cognitive gains to clinical and psychosocial improvements are mixed (Cavallaro et al, 2009; Urben et al, 2012).…”
Section: Extending Neurocognitive Training Paradigms For Treatment Ofmentioning
confidence: 99%
“…Several studies have demonstrated that high-frequency, computerized cognitive training ameliorates deficits in cognitive flexibility among those with schizophrenia (Bellucci, Glaberman, & Haslam, 2003; Dickinson et al, 2010; Urben et al, 2012). Results on generalization of cognitive gains to clinical and psychosocial improvements are mixed (Cavallaro et al, 2009; Urben et al, 2012). Indeed, most studies that yielded improved behavioral outcomes were confounded by the inclusion of psychotherapeutic intervention, which included practice of specific behavioral strategies to improve psychosocial functioning (Bowie & Gupta, 2013; Wykes et al, 2011).…”
Section: Extending Neurocognitive Training Paradigms For Treatment Ofmentioning
confidence: 99%
“…In a recent, randomized, controlled CR study applied individually (40 sessions) to adolescent out‐patients using paper and pencil tasks, Puig et al reported that participants maintained cognitive gains in executive functions, verbal and working memory, and overall composite cognitive scores at 3 months post‐CR intervention. Compared to baseline measures only, cognitive improvements in reasoning and executive function were found 6 months following an 8‐week/16 session computer‐assisted CR intervention among another group of in‐patient adolescents with, or at risk for psychosis …”
Section: Discussionmentioning
confidence: 89%
“…Earlier durability studies with adult schizophrenia patients concluded that training effects endured 6 months and up to 1 year after the cessation of CR treatment. The positive effects of CR for adolescents at risk for, or with, early onset psychosis have also been found to persist at 3 months, 6 months and 12 months post‐intervention . Although effects in schizophrenia are promising, to our knowledge, no durability studies investigating CR and adolescents with 22q11DS currently exist: thus, the durability of CR effects in this population remains unknown.…”
Section: Introductionmentioning
confidence: 99%